Impact of the COVID-19 Pandemic on the Dutch Screening Program for Developmental Dysplasia of the Hip—Delayed Screening and One-Year Outcomes - Jan H. Hinloopen; Demi J. Donker; Joost H. van Linge; Christiaan J. A. van Bergen; Florens Q. M. P. van Douveren; Margret Foreman-van Drongelen; Frederike E. C. M. Mulder; Jaap J. Tolk; Pieter Bas de Witte (Children)
Background/Objectives: In the Netherlands, selective ultrasound (US) screening for developmental dysplasia of the hip (DDH) typically occurs at 3 months of age. During the COVID-19 pandemic, US screening was temporarily halted in Dutch hospitals, with consequent delay in DDH screening and possibly inferior outcomes in DDH patients. Methods: We analyzed 1849 infants screened for DDH during the COVID-19 pandemic (March–August 2020) and 1663 infants screened before the pandemic (March–August 2019). We compared mean age and timing of screening (standard vs. delayed (delayed defined as ≥15 weeks)). For secondary outcomes, we compared DDH patients with delayed screening to standard screening, assessing severity at diagnosis, treatment method and duration, and outcomes at the age of one year, including acetabular index (AI) on radiographs. Results: Mean age at screening was 17.3 weeks during the COVID-19 crisis (2020) vs. 15.8 weeks in the 2019 cohort (mean difference 1.5, 95% CI 1.1–1.8, p < 0.001). Delayed screening occurred in 57.6% of infants in 2020 vs. 36.7% in 2019 (p < 0.001). Patients with DDH with delayed screening (n = 284), compared to standard screening (n = 284), did not differ in mean alpha angle at diagnosis (55.0° vs. 54.4°, mean difference 0.6, 95% CI −0.06–1.25, p = 0.08) and AI at one year (24.0° vs. 24.5°, mean difference −0.5, 95% CI −1.05–0.14, p = 0.13). Conclusions: This study revealed that disruption of healthcare caused by the COVID-19 pandemic resulted in a delay in the Dutch DDH-screening program. However, in this study, delayed screening was not associated with inferior outcomes at the age of one year.